Treatment of Ectopic Mandibular Second Permanent Molar with Elastic Separators - R. Rajesh; V. Naveen; S. Amit; Kusai Baroudi; C. Sampath Reddy; Srinivas Namineni (Case Reports in Dentistry)
Ectopic eruption is a developmental disturbance in which the tooth fails to follow its normal eruption pathway. Ectopic eruption of the second molar is relatively rare. This paper presents the case of thirteen-year-old male with an ectopic mandibular second permanent molar. The condition was corrected with surgical exposure and placement of elastic separators. This case report lays emphasis on the practice of basic methods to obtain acceptable results rather than extensive surgical or orthodontic corrections. It is advised that ectopic teeth should not be neglected especially when it concerns developing caries and malocclusion.